Avaliação de partículas poliméricas como material suporte em reator anaeróbio de leito fluidizado no tratamento de fenol - Sader, Leandro Takano (Universidade Federal de São Carlos, 2005)
This work had as objective studies of the biofilms formation in polymerics particles used as material supports in anaerobic fluidized-bed reactors. Three polymerics supports were tested: polystyrene, PET and PVC, which suffered appropriate acid treatment, in way to provide them superficial characteristics as rugosity, porosity and favorable electric charge, with the purpose of favoring the microbial adhesion. The reactors were inoculated with sludge originating from reactor UASB that treated swine slaughterhouse residue, adapted to the degradation of the phenol by 150 days. The volume of the reactors was of 770cm3, and they operated with ascendant speed of 1,3 times of the flow rate of the minimum fluidization. The phenol concentration varied from 100 to 400mg/L in the feeding of each system, presenting results of removal of phenol of 97%, 98% and 97,5% and removal of DQO of 84%, 88,5% and 87%, respectively for the reactors with polystyrene, PET and PVC, which operated with time of detention hydraulic relative the height of the bed, corresponding to the reactional volume of the reactors (TDHr) of 22 h, 10,6 h and 20,4 h, respectively. The quantification of extracellular polymeric showed better results for the particles of PVC that it presented 0,2 mgCarbohydrate/gParticle and 0,06 mgProteyn/gParticle. However, deformations in those particles harming the acting of the reactor, defining as better support the particles of PET, and in this reactor the percentage of phenol removal was larger for a smaller TDHr.
Keywords: Biotecnologia; Processo anaeróbio; Leito fluidizado; Fenol; Biofilme; Process anaeróbio; Fluidized bed; Phenol and biofilm; ENGENHARIAS::ENGENHARIA QUIMICA